Radioimmunoassay for Human Alpha(1)-Fetoprotein - Silver, Hulbert K. B. (National Academy of Sciences, 1973)
A method of radioimmunoassay has been developed for the quantitation of alpha(1)-fetoprotein in human serum. The assay requires 20 μl of serum, can be completed in 8 hr, and can reproducibly detect concentrations of 20 ng of alpha(1)-fetoprotein per ml of serum. Hence, the method is about 500-fold more sensitive for the detection of alpha(1)-fetoprotein than the Ouchterlony teohnique currently in general use. The procedure is of potential clinical value as an aid in the diagnosis of cancer and a number of noncancerous hepatic diseases. IMAGES: